Influence of the properties of the joining partners on the load-bearing capacity of shear-clinched joints - Wiesenmayer, Sebastian; Graser, Matthias; Merklein, Marion (Journal of Materials Processing Technology, 2020)
Shear-clinching requires a minimum ductility for the punch-sided sheet material. A promising approach to overcome this limitation is a local short-term heat treatment of the upper joining partner in the joining zone. However, the design of heat treatment layouts for high-strength aluminum alloys necessitates fundamental knowledge on the mechanisms in shear-clinching processes in dependence of the properties of both joining partners. Therefore, within the paper, the mechanisms in shear-clinching were analyzed for a common aluminum magnesium alloy of the 5000 series, an alloy of the 6000 series with higher strength and a high-strength alloy of the 7000 series. On the die-side, hot stamped 22MnB5 and the dual phase steel HCT780X was utilized. For upper sheet materials with higher strength, the radial material extrusion of the upper joining partner decreases, which leads to the increase of the material volume in the joining zone and therefore to a larger bottom thickness and interlock. In addition, the decreased penetration of the outer punch results in a larger upper neck thickness. Due to the larger load-bearing cross section and the higher tensile strength, higher forces can be transmitted for high-strength materials. However, the low ductility of high-strength materials results in a failure of the joint at lower displacements and therefore in a decreased energy absorption. The found mechanisms provide the theoretical basis for the design of heat treatment layouts for high-strength aluminum alloys.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Heat treatment; High-strength aluminum; High-strength steel; Joining; Multi-material design